Spaces of participation : dynamics of social and political change in the Arab world - Aboubakr, Randa, 1966-; Jurkiewicz, Sarah; Ait-Mansour, Hicham, 1977-; Freitag, Ulrike (The American University in Cairo Press, 2021)
"Where do people meet, form relations of trust, and begin debating social and political issues? Where do social movements start? In this fascinating collection, scholars and activists from a wealth of disciplinary backgrounds, including sociology, anthropology, history, and political science, take a fresh look at these questions and the factors leading to political and social change in the Arab world from a spatial perspective. Based on original field work in Egypt, Kuwait, Morocco, and Palestine, Spaces of Participation connects and reconnects social, cultural, and political participation with urban space. It explores timely themes such as formal and informal spaces of participation, alternative spaces of cultural production, space reclamation, and cultural activism, and the reconfiguring of space through different types of contestation. It also covers a range of spaces that include sports clubs, arts centers, and sites of protest and resistance, as well as virtual spaces such as social media platforms, in the process of examining the relationships and tensions between physical and virtual space"--